2009
DOI: 10.1182/blood-2009-03-212852
|View full text |Cite
|
Sign up to set email alerts
|

Pim kinase inhibitor, SGI-1776, induces apoptosis in chronic lymphocytic leukemia cells

Abstract: IntroductionPim (provirus integration site for Moloney murine leukemia virus) family proteins are highly conserved serine/threonine kinases that have been implicated in cancer progression and the development of resistance to chemotherapeutic agents (for a review, see Shah et al 1 ). Three Pim kinases have been identified to date, Pim-1, -2, and -3, and elevated expression of Pim kinases have been detected in hematologic malignancies and in certain solid tumors. [2][3][4][5] These kinases have similar active si… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

6
225
2
1

Year Published

2010
2010
2023
2023

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 184 publications
(234 citation statements)
references
References 47 publications
6
225
2
1
Order By: Relevance
“…Previous studies have shown an increase in the expression of the PIM2 kinase in CLL cells by using qPCR and intracellular fluorescence-activated cell sorting (FACS) staining [Cohen and colleagues (28); and Chen and colleagues, (41)]. To verify these results in our CLL cohort (Supplementary Table S1), we investigated the expression level of all three PIM kinases at the transcriptional and protein levels.…”
Section: Pim1 and Pim2 Are Overexpressed And The Cxcr4 Receptor Is Hymentioning
confidence: 65%
“…Previous studies have shown an increase in the expression of the PIM2 kinase in CLL cells by using qPCR and intracellular fluorescence-activated cell sorting (FACS) staining [Cohen and colleagues (28); and Chen and colleagues, (41)]. To verify these results in our CLL cohort (Supplementary Table S1), we investigated the expression level of all three PIM kinases at the transcriptional and protein levels.…”
Section: Pim1 and Pim2 Are Overexpressed And The Cxcr4 Receptor Is Hymentioning
confidence: 65%
“…Immunohistochemical staining of tissue microarrays (TMA) reveals that PIM1 is expressed in 87% of mantle cell lymphomas (MCL; Hsi et al, 2008), 76% of chronic lymphocytic leukemia/small lymphocytic lym phoma (CLL/SLL; Chen et al, 2009), and 48 and 42% of dif fuse large B cell lymphoma (DLBCL) and FL, respectively. PIM2 is detected in 42% of DLBCL and between 24% and 30% of FL, MCL, and CLL/SLL (Fig.…”
Section: Resultsmentioning
confidence: 99%
“…More and more evidence has demonstrated that pim-1 kinase plays an important role in tumor progression, including prostatic cancer, laryngeal cancer, lymphocytic leukemia, and head and neck squamous cell carcinomas (14,(24)(25)(26)(27)(28)(29). However, to date, the role of Pim-1 in the development of ESCC has not yet been investigated.…”
Section: Discussionmentioning
confidence: 99%
“…More and more evidence has demonstrated that Pim-1, a proto-oncogene encoding a serine/threonine protein kinase, plays an essential role in cell survival, cell proliferation, cell differentiation, cell cycle, and cell apoptosis (7)(8)(9)(10)(11)(12)(13)(14), especially in the occurrence and development of tumors (15)(16)(17)(18)(19)(20). Therefore, the rapidly increasing knowledge on the role of the Pim-1 in cancer will hopefully provide useful molecular markers for detection and prognosis of tumor.…”
Section: Introductionmentioning
confidence: 99%